Features of selection of anticoagulant therapy in patients with critical ischemia of lower extremities after reconstructive operations - I. I. Katelnitsky; Igor I. Katelnitsky; E. S. Livadnyaya (Медицинский вестник Юга России, 2018)
Objective: to improve the results of treatment of patients with obliterating atherosclerosis with critical ischemia of the lower extremities by individual selection of anticoagulant therapy for the prevention of thrombosis aft er reconstructive surgery on the arteries of the lower extremities. Materials and methods: 82 patients were divided into 2 groups: 1 group (48 patients) - reconstructive surgery on the arteries of the lower extremities and anticoagulant therapy under the control of the coagulogram. 2 group (34 patients) - reconstructive operations with the selection of anticoagulant therapy with the help of hemostasiogram indicators and the T-2 thrombodynamics test. Results: Out of 48 patients in the 1 study group, a good eff ect was observed in 36 patients (75.00%), in 9 (18.75%) - satisfactory, and in 3 cases (6.25%) - unsatisfactory. In the 2nd group: good results - 33 (97.06%) patients, and in 1 (2.94%) patients - satisfactory. Unsatisfactory results were not. Th e number of repeated operations within 1 year, performed in the 1st group, was statistically signifi cantly 2 times greater than in the second group. All the second operations are associated with the development of thrombotic complications. With a combination of the majority of hemostasiogram and «Trombodynamics T-2» tests, the dose of heparin therapy was adjusted, increasing by 2500 units, i.е. the patient received 7500ED 4 p / day. If during the «T-2 thrombodynamics» and coagulogram on the 6th day aft er surgery, hypercoagulation was determined, then the dose of heparin increased again by 2500 units. Conclusions: Comparative analysis of hemostasiogram indices in the fi rst hours aft er the performed operative treatment is not very useful for predicting the frequency of thrombotic complications, while 6 days aft er operative treatment it indicates the presence of statistically signifi cant diff erences between the two study groups. Th at indicates a more adequate selection of a dose of heparin in the second group.